A study of beliefs towards mental illness among teachers in Sikar city, Rajasthan - Navneet Kaur; Nilam S. Behere; Anjali S. Kulkarni (Indian Journal of Psychiatry)
Background: Understanding the significance of adolescents’ mental health, school-based mental health interventions are being implemented with the help of teachers globally. Aim: Owing to the dearth of literature concerning the beliefs, and stigma among the teachers, the present study was conducted with an aim to study the mental health beliefs among teachers. Methods: This is a cross-sectional study conducted among randomly selected teachers teaching in government and private schools of Sikar city of Rajasthan. A general sociodemographic questionnaire, Beliefs Towards Mental Illness Scale, and a questionnaire about prior exposure to mental health issues was administered. Stata 15.0 was used for statistical analysis, and independent t-test and one-way analysis of variance test were applied to find out associations. Results: Majority of the participants were in age group of 31-40 years, married, and postgraduate. The mean Beliefs Towards Mental Illness Scale score of 147 teachers was 49.95 ± 17.34 of 105. Only 2% of the study participants have ever received training related to mental health issues. Teachers who had prior exposure to mental health issues, residing in semi-urban and urban areas showed more positive beliefs. Conclusion: Study participants have displayed negative beliefs toward mental health. This brings to light the important interventions like creating knowledge and awareness among the study population by conducting trainings. More research is needed to explore the mental health beliefs among the teachers.